STANDAR PRIBADI MAHASISWA: KUNCI SUKSES AKADEMIK DAN PENGEMBANGAN MENTALITAS MENURUT KH. HASYIM ASY'ARI - Alif, M. Wildan; Sopingi, Imam; Hidayati , Athi’ (PAI FAI UNHASY Tebuireng Jombang, 2025)
This research examines KH. Hasyim Asy'ari's thoughts on the ideal standard of student personality as the key to successful education. Departing from the challenges of moral degradation and the spirit of learning among students, this study aims to examine the concept of education based on Islamic values rooted in pesantren heritage. The method used is literature research by examining the works of KH. Hasyim Asy'ari. The results show that eight standards of student personality-such as purity of heart, straight intention, time management, patience, ethics, and avoiding obstacles to learning-are important foundations in the formation of students' morals and intellectuality. The implication is that education slamic morals and values can form a generation with integrity, adaptive to globalization, and based on strong spirituality.